KENYAN EDUCATION IN THE WAKE OF CONSUMERISM: EFFECTS ON FUNDING AND QUALITY - Kituko, Simiyu Catherine (Journal of Education and Practice, 2020)
Education is key for any form of personal or societal development. Citizens who can read, calculate, and think critically are a country's great resource as they have better economic opportunities, higher agricultural productivity, healthier children, and better reproductive health. In her drive towards realization of the Vision 2030 therefore, Kenya highlights education and training as crucial components of the Social Pillar. This is with the understanding that knowledge is important for growth and development of economies. Yet, it is not just education for its own sake, but quality education to serve as a lever for personal development so that the capable and active citizens can in-turn be the strongest lever for long term sustainable change. There is however an emerging trend, consumerism, which thrives on pleasure seeking morality and hedonistic lifestyle while promoting intellectual inactivity. One only needs to have money to pay, often, for one's wants. How this money is obtained is not the issue. This certainly is at crossroads with the ideals of a holistic education which emphasizes virtues such as creativity, honesty and social integration. The purpose of this study was to examine the complexity of funding for quality education in a consumer heightened economy. The method of investigation was content analysis. The paper recommends an overhaul in the Kenyan education award system to ingrain human values of honesty and integrity. This would enhance the policy of quality education for sustainable economic growth.